Prevalence of beta hemolytic Streptococcus in patients with acute pharyngoamigdalitis in a Chachapoyas, Amazonas hospital - Guevara D, José María (2008)
Introduction: There are numerous Chachapoyas patients with acute pharyngoamigdalitis and clinical non suppurative complications caused by Streptococcus pyogenes. Design: Transversal study. Setting: Hospital I Higos Urco, EsSalud, Chachapoyas, Amazonas, and Instituto de Medicina Tropical Daniel A. Carrion, Universidad Nacional Mayor de San Marcos. Participants: Patients with acute pharyngoamigdalitis. Interventions: One hundred and forty-eight randomized outpatient subjects attending an ear, nose and throat office for clinical symptoms compatible with acute pharyngoamigdalitis had a sample of pharynx and tonsils taken with a cotton swab and sent in Amies with carbon medium (Difco) to the Instituto de Medicina Tropical Daniel A. Carrion to be processed. Main outcome measures: Presence of beta hemolytic Streptococcus and other bacteriae. Results: Positive cultures revealed mainly Enterobacteriae (49,1%). Only 5 beta hemolytic Streptococcus were isolated: one Streptococcus pyogenes, three Streptococcus agalactiae and one group G Streptococcus, all sensitive to betalactamics, macrolides and lincosamides. Conclusions: We suggest to do complementary studies with antiestreptolysin O determination.